2020
DOI: 10.1097/corr.0000000000001161
|View full text |Cite
|
Sign up to set email alerts
|

Residency Selection Preferences and Orthopaedic Career Perceptions: A Notable Mismatch

Abstract: Background Despite near-equal enrollment of males and females in medical schools, orthopaedic surgery continues to have one of the lowest percentage of female orthopaedic residents. This suggests there may be factors that specifically influence females to select other specialties. Some of these possible reasons have been explored in other studies; however, in this study, we sought to identify latent or unobserved variables that may be influencing this difference by conducting an explanatory factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 24 publications
1
18
0
2
Order By: Relevance
“…Studies detailing associations among orthopaedic institutions’ faculty diversity, resident diversity, and the diversity of the applicant pool of medical students suggest the perception of diversity is an important factor. 27 , 28 , 36 , 48 Additional investigation of these topics is warranted, for which our initial study may serve as a benchmark and impetus for increased participation from professional leagues, allowing for more robust data collection in future iterations.…”
Section: Discussionmentioning
confidence: 99%
“…Studies detailing associations among orthopaedic institutions’ faculty diversity, resident diversity, and the diversity of the applicant pool of medical students suggest the perception of diversity is an important factor. 27 , 28 , 36 , 48 Additional investigation of these topics is warranted, for which our initial study may serve as a benchmark and impetus for increased participation from professional leagues, allowing for more robust data collection in future iterations.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, a UK study assessing the effects of the ‘Hidden Curriculum’ across 13 medical schools discovered that 66% of students had heard negative comments about surgery and 27% altered their career plans as a result. 19 Furthermore, Whitaker et al 20 reported 95% of female medical students perceived orthopaedics to be a ‘male dominated speciality’, and 60% felt orthopaedics ‘requires physical strength’. Although orthopaedics is more physically demanding than specialities such as ophthalmology, modern-day techniques and technology have made it easier for women to operate.…”
Section: The Hidden Curriculummentioning
confidence: 99%
“…Although the first latent factor for males consisted of "prestige," "income potential," "grade or step scores," and "competitiveness of residency program." By identifying the multifactorial areas that may be inadvertently discouraging females from applying, orthopaedic residency programs may be able to better address those issues and attract the best talent of both genders [42]. For example, it is important to teach female medical students that orthopedic surgery has greatly progressed from the brute force discipline of the past, with new techniques and equipment decreasing the strength requirement [43].…”
Section: Orthopaedic Disparitiesmentioning
confidence: 99%
“…Although females pursue orthopaedic residency less frequently than males, performance during residency should not bias their future selection. Whitaker et al [ 42 ] reported, by surveying a cohort of medical students at a single institution, that both male and female students ranked “work-life balance” and “variety in specialty” among the top three most important preferences. Females ranked “range of practice options,” higher than males, and males ranked “previous exposure to the specialty” higher than females.…”
Section: Orthopaedic Disparitiesmentioning
confidence: 99%
See 1 more Smart Citation